Bio-ingredients assisted synthesis of Fe doped zinc oxide nanostructures: Study on structural, optical, morphological and thermal properties. Issue 24 (15th December 2021) - Ranjithkumar, B.; Ranjith Kumar, E.; Ramalingam, H.B.; Rahale, C. Sharmila; Mahmoud, Mohamed H.H.; Binyaseen, Adel M.; Keshk, Ali A.; El-Metwaly, Nashwa M.
Abstract: Bio-ingredients (animal urine and honey) assisted synthesis of Fe doped ZnO nanostructures has been reported. The structural, optical, morphological, and thermal properties of Fe–ZnO nanostructures were investigated using XRD, FTIR, FESEM, TEM, and TGA. The average crystallite size of Fe–ZnO nanostructures made with animal urine is 34.2 nm, while those made with honey have an average crystallite size of 8.8 nm. It indicates that the size of Fe–ZnO nanostructure crystallites was determined in part by reaction time. FESEM was used to verify the nanostructures of the spherical shaped nanoparticles, and the honey Fe–ZnO sample showed a uniform distribution of particles. EDX analysis confirmed the existence of Zinc (Zn), Iron (Fe), and Oxygen (O) in the synthesized sample. According to TEM photos of Fe–ZnO nanostructures, the particle size of the samples is well correlated with the crystallite size determined by XRD. The thermal stability of Fe–ZnO nanostructures, as well as the effect of these natural ingredients on thermal stability, has been investigated. The surface charge and Zeta potential value of Fe doped ZnO nanoparticles using honey and Animal urine have been analyzed. The obtained values confirm the honey used Fe–ZnO nanoparticles has higher stability (−22.7 mV) than the animal urine assisted sample (−10.1 mV).